The Limiting Degree of Linear System Aperiodic Stability and the Choice of Industrial Regulator Parameters - A. V. Tatarinov; A. M. Tsirlin (Моделирование и анализ информационных систем, 2015)
The problem of a limiting degree of linear system stability is investigated. The conditions are received, where roots nearest to an imaginary axis are valid. When fulflling these conditions the limiting degree of stability for a typical industrial object with delay and "serial" laws of regulation is found.